Dengue encephalitis as a sole presentation of dengue fever in a child, is it a separate clinical entity? - Lourembam, Radhapyari; K., Rahees V.; C., Shyamsunder Singh (International Journal of Contemporary Pediatrics, 2023)
Dengue fever is one of the common viral infections in tropical areas, especially in India. Though classically non-neurotropic in nature, recent literature has documented dengue viral neurotropism, suggesting possible elements of direct encephalitis. However, limited reports are available in paediatric age groups. Here we report a case of dengue encephalitis in a 3-year 6 months-old male child from Imphal, Manipur, India who presented with a history of fever, altered sensorium, and seizures. The anti-dengue immunoglobulin M antibodies were positive in serum. Cerebrospinal fluid analysis showed lymphocytic pleocytosis with elevated proteins and normal glucose. Neuroimaging was unremarkable. We also ruled out other causes of encephalitis by appropriate investigations. Our case did not have the typical salient features of dengue fever and recovered fully with the supportive treatment on time. The case highlights that dengue encephalitis may present even in the absence of neuroimaging findings and classical clinical signs of dengue fever. Hence, dengue encephalitis should be suspected in a child with fever with altered sensorium and seizures, especially in areas where dengue fever is endemic.